2020
DOI: 10.1007/s10681-020-2562-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, stability and heritability for quality and yield characteristics in provitamin A cassava varieties

Abstract: Cassava is widely consumed in many areas of Africa, including Ghana, and is a major part of most household diets. These areas are characterized by rampant malnutrition, because the tuberous roots are low in nutritional value. Provitamin A biofortified cassava varieties have been developed by the International Institute for Tropical Agriculture, but adoption of these varieties in Ghana will largely depend on their agronomic performance, including fresh root yield, dry matter content, resistance to major pests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
4
12
1
Order By: Relevance
“…We generally observed high heterozygosity across identified genetic groups, indicating a high proportion of genetic variance (allelic variation) across locus in our populations. Taken together, these results show that Admix-Group, Bitter-Group, Amazonas-Group and NE-LandRaces exhibited a higher genetic diversity compared to the rest of the groups and may be explored for heterotic responses in future breeding efforts as recently developed (Peprah et al 2020).…”
Section: Genetic Diversity Estimationmentioning
confidence: 60%
“…We generally observed high heterozygosity across identified genetic groups, indicating a high proportion of genetic variance (allelic variation) across locus in our populations. Taken together, these results show that Admix-Group, Bitter-Group, Amazonas-Group and NE-LandRaces exhibited a higher genetic diversity compared to the rest of the groups and may be explored for heterotic responses in future breeding efforts as recently developed (Peprah et al 2020).…”
Section: Genetic Diversity Estimationmentioning
confidence: 60%
“…This can result in multiple and, perhaps, contrasting preferences that vary according to the user’s role within the food chain, implying that the input and decision‐making roles of different users is of primary importance in crop breeding. Breeding programs have historically focused on yield and disease resistance to face the challenges of food security in terms of feeding a growing population (Ceballos et al ., 2004; Manu‐Aduening et al ., 2006; Ojulong et al ., 2008; Ceballos et al ., 2020), and on malnutrition and safety issues (Adenle et al ., 2012; Peprah et al ., 2020; Xing et al ., 2020), with lower priority on post‐harvest quality characteristics, and processor and consumer demand. In addition, information on product characteristics is often overly simplified by not including information on the optimal range or description that would help breeder’s ability to meet user needs.…”
Section: Introductionmentioning
confidence: 99%
“…The AUC analysis revealed that the stability of β-carotene in TMS 01/1412 gari ranged from ESL (least stable) to SPB (most stable) whereas the stability of β-carotene in TMS 01/1371 gari ranged from ESL (least stable) to SAC (most stable). The differences in the stability and retention capacities between the two biofortified gari across all the experiments may be attributed to genetic influences [15,19,20]. To further support this inference, Bechoff et al [21] recently reported marked differences in the retention of carotenoids during production of biofortified gari from TMS 01/1371, 01/1412 and 01/1368 respectively.…”
Section: Discussionmentioning
confidence: 87%